Cigarette Smoking and Alcohol Use among Adolescents and Young Adults with Asthma - Elizabeth Burgess Dowdell; Michael A. Posner; M. Katherine Hutchinson (Hindawi Limited, 2011)
Asthma is one of the most common, serious chronic diseases in pediatric and young adult populations. Health-risk behaviors, including cigarette smoking and alcohol use, may exacerbate chronic diseases and complicate their management. The aim of this study was to longitudinally analyze rates of cigarette smoking and alcohol use in adolescents and young adults who have asthma and those who do not have asthma. A secondary analysis of data from the National Longitudinal Study of Adolescent Health was undertaken. Individuals with asthma were found to exhibit increasing rates of cigarette smoking and alcohol use as they aged. When an adolescent with a chronic health issue begins health-risk-taking behaviors, behavior change interventions must be planned. Pediatric nurses, practitioners, and clinicians are uniquely positioned to assess for health-risk behaviors in youth with asthma and to intervene with plans of care that are tailored for the needs of this vulnerable population.